Pengaruh Melemahnya Nilai Tukar Rupiah, BI Rate Dan Naiknya Harga Bahan Bakar Minyak Terhadap Kinerja Perbankan Syari’ah Di Indonesia - Andriani (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2016)
Banking development in Indonesia is really influenced by the condition of economic macro. The dynamic fundamental change of economic macro makes banking world apply a strategy to stand and develop. Even though the Syari’ah banking practice in Indonesia that applies profit sharing system is expected independent from the fundamental of economic macro, the decision made cannot be separated from the fundamental of economic macro. The decrease of Rupiah exchange value, the decrease of BI rate, and the increase of fuel price are expected becoming positive signal for Syari’ah banking in Indonesia. This research aims at explaining the relation between the fundamental variables of economic macro and Syari’ah banking works. This research employed an explanatory research design. The population is all Syari’ah banks that expose the monetary report in 2009-2014. There are 11 Syari’ah public banks, 24 Syari’ah companies, and 31 Syari’ah office channelings. The findings reveals that (1) the decision of BI to increase BI rate will be applied if the number of money in society are too much; in the contrary, if the number of money in society are too little, BI will decrease BI rate. From analyzing the data, it shows that BI rate influences positively to Syari’ah banking works. (2) Inflation influences positively to Syari’ah banking works; it means that if inflation increases, Syari’ah banking works becomes better. If the communities ability to buy decrease, the demand of money increase more. This makes syariah banks do no have idle money. (3) the contribution of money exchange variable, BI rate, and inflation influence the Syari’ah banking works. The contribution of X1, X2, and X3 to Y can be seen from R2 (68,7 %), and 31,3 % is influeced by the exchange money variable, PDB, product variation, profit sharing, and promotion.